TWIST: a tree–based web service indication scheme for service tracking in vehicular ad hoc networks. (22nd December 2014) - Lee, Yu–Hong; Dow, Chyi–Ren; Chueh, Chih–Yu; Hwang, Shiow–Fen
Because of the progress of modern automobiles, it is possible to use vehicles as sensors to gather information. This study proposes a geo–aware tree–based service–tracking scheme to locate a specific service in a particular area. The virtual backbone is predefined according to the main roads in the city. It consists of geo–grids and is further organised into a tree structure. The tree structure, which is the higher layer of the virtual backbone, can be used to facilitate service location tracking because any grid inside the tree has only one route to the root. On the basis of footprints from services on the branches of the tree, it is easy to find a specific service and access data of interest in vehicular ad hoc networks (VANETs). The experimental results indicate that the proposed approach outperforms both ad hoc on–demand distance vector (AODV) and the centralised scheme regarding the tracking success rate and service–tracking time.